The Socio-Economic Impact of Refugees on the Neighboring Countries: The Case of Sherkole Refugee Camp, Western Ethiopia (Global Journal of Human-Social Science, 2018)
This study aimed at examining the socio-economic impact of refugees on the neighboring countries the case of Sherkole refugee camp. With this Refugee as people crossing international borders in order to escape conflict or Human right violation have been a central focus of international relations. However, the world refugee problem is caused by a variety of reasons which including massive violation of human right, direct and structural violence, war, internal conflict, ethnic and religious strife, direct political persecutions and economic and natural disasters. Likewise, majorities of the mass movements of refugees in the contemporary world are caused by ethnic conflict, natural disasters and shaping of socioeconomic imbalance. As a result they influence the socio-economic condition of the host countries. This study aims to investigate and assess the socio-economic impacts of the Sherkole refugee camp on the host community who are living around the camp in western Ethiopia. In the study process qualitative sampling technique was used by employing purposive selected key informants, field observation and focus group discussion. The study explained the influx of refugees in Sherkole camp impact positively and negatively the social and economic condition of the host community. Socially host community acquired knowledge and skills from refugees. On the other side they promoted crime and theft to the host community. Economically, the host communities are benefited from the presence of refugees by selling the local product and buying from them goods and service by the low price. In the contrary, their presence leads for the dramatic change of goods and service and food price in the market. Basically refugee camp set as a temporary settlement to serve refugee for the short period of time.
Keywords: socio-economic; impact